Examining The Factors That May Restrict Teacher Candidates To Access Recreational Activities - Recep Öz; Mehmet Yazıcı; Murat Tolga Kayalar; Yasemin Çakmak Yıldızhan (Sakarya University Journal of Education)
The purpose of the present study is toinvestigate the recreation obstacles of teacher candidates in terms ofdifferent variables. A total of 178 teacher candidates (male: 108, female:70)from Faculty of Education at Erzincan Binali Yıldırım University voluntarilytook part in the present study to meet this purpose in 2018. 94 of theparticipants were from the department of computer education and instructionaltechnology, and the rest of them was from the department of psychologicalcounseling and guidance. The instrumentnamed “Leisure Time Obstacle Scale” was used during the study, which wasdeveloped by Alexandris and Carroll (1997), adopted to Turkish context byGürbüz and Karaküçük (2007), and revisedby Gürbüz et al., (2007). Independent sample t-test and One-way ANOVA testswere used to answer the research questions. Tukey test was employed as aposthoc analysis to figure out the differences among the categories.Consequently, a nonsignificant result was observed for the subfactors of LTOSdepending on the variables including gender, class level, and the sports branchbeing interested. However, a significant difference was found at the friend andtime subfactors of the LTOS in terms of department category (p<.05).Furthermore, a significant difference was also observed at friend subfactor ofLTOS for achievement level. Finally, a significant difference was also detectedfrom the analysis results for the information subfactor of LTOS in terms of sportsbranch being interested.